The University faculty-researchers' assessment of their research involvement and practice of research-infused instruction. - Sodusta, Donne Jose P
This descriptive study sought to describe the profile of the West Visayas State University faculty-researchers as of Academic Year 2005-2006, and determine their assessment of their research involvement and the extent of their practice of research-infused instruction, and the problems they encountered in the implementation of the said activities. An a Assessment Questionnaire for Faculty-Researchers (AQFR) which has been subjected to panel validation and pilot testing was used to gather data for the study. the questionnaire was to 47 randomly selected sample, representing 52 percent of the entire population of the University faculty-researchers. However, only 45 faculty-researchers comprising 96 percent of the sample duly accomplished the questionnaire. The data were tabulated, organized and subjected to descriptive statistical analysis., The findings of the study revealed that the profile of the University-faculty-researchers in terms of their personal characteristics showed that a large majority were females and between the ages of 41-51 years and above. On the professional aspect, a large majority were master's and or doctor's degree holder with the rank of assistant professor or associate professor, handling at least 4-6 or more classes per semester and an administrative position and with more than 10 years of teaching experience in the University. In terms of research involvement, the faculty-researchers as well as a whole, were only sometimes involved in research related activities, rarely participated in research roles and had low research outputs which were concentrated at the institutional level. In terms of the practice of research-infused instruction, this approach was often applied in the areas of course objectives and content and only sometimes applied in course evaluation, learning opportunities, and pedagogy. Problems like time constraints, resource limitations or availability and difficulties encountered in conducting researches hindered faculty-researches' involvement. In addition to these, students' weak research knowledge, skills and attitudes limited the faculty-researchers' practice of research-infused instruction in the classroom. Based on the findings, it can be deduced that although senior and well - experienced faculty-researchers dominate research endeavors in the University, their research involvement and practice of research-infused instruction is limited because of the University's institutional requirements, internal structures, and their personal conditions.